2014
DOI: 10.1364/oe.22.010091
|View full text |Cite
|
Sign up to set email alerts
|

Hollow antiresonant fibers with low bending loss

Abstract: We first use numerical simulations to show that bending losses of hollow antiresonant fibers are a strong function of their geometrical structure. We then demonstrate this by fabricating a hollow antiresonant fiber which presents a bending loss as low as 0.25 dB/turn at a wavelength of 3.35 μm and a bend radius of 2.5 cm. This fiber has a relatively low attenuation (<200 dB/km) over 600 nm mid-infrared spectral range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
129
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 152 publications
(134 citation statements)
references
References 20 publications
4
129
0
1
Order By: Relevance
“…In Kagome-type hollow core fibers with a hypocycloid core surround, several studies have shown a dependency between the leakage loss of the fiber and its cladding structure [4,5], and recent works have already established that leakage loss can be significantly reduced when the curvature of the arcs forming the core boundary is increased [6][7][8], although no clear physical explanation has been provided for this behavior. A more recent family of hollow antiresonant fibers, already highlighted for its low loss in the infrared [2] and for its relatively low bending loss at large mode field diameters [5], consists of a simpler design in which the air-core is surrounded by a number of touching or non-touching circular capillaries [1,9]. These fiber types offer a better platform to try to understand the effect that the curvature of the membranes surrounding the core has on the overall loss, since different curvatures can be obtained while keeping unchanged key geometrical parameters [5,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Kagome-type hollow core fibers with a hypocycloid core surround, several studies have shown a dependency between the leakage loss of the fiber and its cladding structure [4,5], and recent works have already established that leakage loss can be significantly reduced when the curvature of the arcs forming the core boundary is increased [6][7][8], although no clear physical explanation has been provided for this behavior. A more recent family of hollow antiresonant fibers, already highlighted for its low loss in the infrared [2] and for its relatively low bending loss at large mode field diameters [5], consists of a simpler design in which the air-core is surrounded by a number of touching or non-touching circular capillaries [1,9]. These fiber types offer a better platform to try to understand the effect that the curvature of the membranes surrounding the core has on the overall loss, since different curvatures can be obtained while keeping unchanged key geometrical parameters [5,10].…”
Section: Introductionmentioning
confidence: 99%
“…A more recent family of hollow antiresonant fibers, already highlighted for its low loss in the infrared [2] and for its relatively low bending loss at large mode field diameters [5], consists of a simpler design in which the air-core is surrounded by a number of touching or non-touching circular capillaries [1,9]. These fiber types offer a better platform to try to understand the effect that the curvature of the membranes surrounding the core has on the overall loss, since different curvatures can be obtained while keeping unchanged key geometrical parameters [5,10]. In a more recent study, a fiber Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, rapid progress has been made in developing low-loss and bendable HCFs comprising an antiresonant, negative curvature core boundary. In antiresonant hollow-core fibers (AR-HCFs), the precisely designed core wall minimizes the optical intensity in the glass structure and reduces losses [2,[4][5][6][7][8]. The first demonstration of an AR-HCF was based on a Kagome structure [3].…”
Section: Introductionmentioning
confidence: 99%
“…This fiber design achieved relatively low transmission loss and broad-band guidance due to the low coupling between their core and cladding modes. Subsequently, various designs of AR-HCF based on a negative curvature core wall with improved optical properties were demonstrated [4][5][6][7][8]. Recently, non-touching capillaries core wall fibers were demonstrated as an attempt to further reduce the transmission losses and at the same time, broaden the transmission window [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation